Fikih Mangrove: Formulasi Fikih Lingkungan Pesisir Perspektif Eko-Syariah - Mufid, Moh. (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2017)
Abstract: This article is a study of mangrove management in eco-sharia perspective. Conservation efforts in the coastal areas must be constructed based on religious values ​​so that it is expected to create a collective attitude of environmental awareness among coastal communities. Eco-sharia as an approach can provide a new paradigm related to the preservation of the coastal environment with anthropo-cosmic insights. The concept of eco-ecology and ecosystem can also provide a comprehensive understanding in the effort to support the existence of coastal environment jurisprudence. Normatively, the perspective of Islamic jurisprudence on mangroves preservation can be built through an in-depth understanding of Islamic recommendations in rehabilitating mangrove habitats in coastal area; Procedure of mangrove land conversion based on consideration of principle of benefit; Thus, it is urged that local governments to issue regulations to manage mangrove preservation in a sustainable manner. Abstrak: Artikel ini merupakan kajian pengelolaan mangrove dalam perspektif eko-syariah. Upaya pelestarian di wilayah pesisir harus dikonstruksi berbasis nilai-nilai religius sehingga diharapkan mampu melahirkan sikap kesadaran lingkungan secara kolektif di kalangan masyarakat pesisir. Eko-syariah sebagai suatu pendekatan dapat memberikan paradigma baru terkait pelestarian lingkungan pesisir dengan wawasan antropokosmis. Konsep ekoteologi dan ekosofi juga dapat memberikan pemahaman yang komprehensif dalam upaya mendukung eksistensi fikih lingkungan pesisir. Secara normatif, fikih mangrove dapat dibangun melalui pemahaman secara mendalam tentang anjuran Islam dalam merehabilitasi habitat mangrove di pesisir; prosedur alih fungsi lahan mangrove berdasarkan pertimbangan asas manfaat-mafsadat; keniscayaan pemerintah daerah menerbitkan regulasi untuk mengatur pengelolaan mangrove secara berkelanjutan.